A novel method Hybrid Photo-electrocatalytic Oxidation for the treatment of 3, 4-dimethyaniline wastewater: Degradation mechanism and synergistic effect. (December 2020) - Li, Zhaodong; Li, Meng; Tang, Jianwei; Zhang, Qian; Jiang, Yiheng; Li, Haoyu
Graphical abstract: Highlights: An efficient mothed for the treatment of 3, 4-DMA. Degradation and synergistic mechanisms during degradation. Controlling factors for synergistic degree. Abstract: 3, 4-dimethyl-aniline is a stubborn organic matter and widely appears in many industrial wastewaters. A novel method Hybrid Photo-electrocatalytic Oxidation (HPECO) combining Photocatalytic Oxidation (PCO) with Electrocatalytic Oxidation (ECO) was established to treat it. The removal efficiencies were compared among HPECO, PCO and ECO systems and the result suggested HPECO was 2.45 and 1.14 times higher than the sum of other two systems for 3, 4-DMA and TOC removals, separately. Furthermore, a three-stage mechanism was proposed in HPECO process by cyclic voltammetry, ESR and quantitative determination of HClO and a whole degradation pathway was deduced by GC–MS. In the first stages, HClO attacked the side chains of 3, 4-DMA and oxidized it into 3, 4-dimethylphenol, 2-amino-6-methylbenzoic acid and 1, 2, 4-benzoic acid. In the last two stages, these intermediates were further degraded until mineralization, under the co-oxidation of chlorine radical species (CRS) and OH. In addition, synergistic effect was studied with generating reason and controlling factors. UV irradiation and applied voltage could increase the yields of OH and CRS. Electrochemical process could also accelerate the production of OH through O2 evolution reaction. The existence of OH could facilitate the transform of 3, 4-DMA into the intermediates containing COOH groups, which provided the bridge substances for CRS and HClO to achieve the rapid selective oxidation. The further investigation found that synergistic effect was positively correlated with current density and negative correlated with pH and UV power. Finally, pharmaceutical wastewater was treated with this novel method and it can be successfully removed to meet the Chinese national sewage discharge standard after 30 h degradation.